Spinal Cord Injury Therapy - Ibarra, Antonio; García-Vences, Elisa; Guízar-Sahagún, Gabriel (IntechOpen, 2019)
Spinal cord injury (SCI) is one of the main pathologies causing significant loss of neurological function. Therefore, a variety of pharmacological and non-pharmacological therapies are the aims of several studies. To provide the best care, it is important to know and understand the therapeutic approaches that have shown important progress in this topic. This book contains eight chapters that are divided into three sections: Introduction, Pharmacological Therapies, and Non-Pharmacological Therapies. The authors of the chapters deal with the pathophysiology of SCI, the effect of antioxidant and immunosuppressive agents, stem cell-based therapies, the use of cultured cells for transference or transplantation, and the application of non-invasive modalities (transcutaneous electrical spinal cord stimulation, etc.) for SCI rehabilitation.